ANALISIS PELAKSANAAN PROGRAM SEKOLAH RAMAH ANAK (SRA) DI SMP NEGERI 5 PEKANBARU - Titin Sumarni; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the occurrence of violence or bullyingbetween students and educators in the school. The formulation of this research problemis How the Implementation of the Children Friendly School Program (SRA) at SMPNegeri 5 Pekanbaru. Purpose of this research is to know and to analyze theimplementation of the Children Friendly School Program (SRA) at SMP Negeri 5Pekanbaru. This research was conducted at SMP Negeri 5 Pekanbaru Sultan SyarifQasim street No. 155 Rintis village, fifty subdistrict, Pekanbaru. This research wascarried from June to July 2019. This research is a qualitative descriptive method. Thisresearch use data collecting observation, interviews, and documentation technique. Thevalidating data uses with source and triangulation technique. So the results in this studyindicate that the Implementation of Children Friendly School has run quite well. Butthere any some that have not property yet, including the persistence of violence byeducators and bullying in the school, although it has diminished, but is still within thelimits of reasonableness, there are no facilities for inclusion children, there were suchas some facilities damaged leaky roofs, broken toilets, washbasins, unavailability ofchild rights training for educators and education staff in the school, there is no Decree(SK) for the implementation of Children Friendly School (SRA).Key Words : Implementation, Children Friendly School (SRA)